The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7448/ias.19.1.20642
|View full text |Cite
|
Sign up to set email alerts
|

Divergent adherence estimates with pharmacokinetic and behavioural measures in the MTN‐003 (VOICE) study

Abstract: IntroductionIn the Microbicide Trial Network MTN-003 (VOICE) study, a Phase IIB pre-exposure prophylaxis trial of daily oral or vaginal tenofovir (TFV), product adherence was poor based on pharmacokinetic (PK) drug detection in a random subsample. Here, we sought to compare behavioural and PK measures of adherence and examined correlates of adherence misreporting.MethodsWe included participants with PK and behavioural data from VOICE random subsample. Behavioural assessments included face-to-face interviews (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Indeed, several participants in this study suggested that objective testing with consequences, such as study termination, would be the best way to ensure participants took study products. While participants had diverging opinions on the pros and cons of face to face (FTF) versus ACASI modalities for improving honest responses, independent data from VOICE indicate that none of the behavioral assessments in the trial had any accuracy in estimating product use [8, 21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several participants in this study suggested that objective testing with consequences, such as study termination, would be the best way to ensure participants took study products. While participants had diverging opinions on the pros and cons of face to face (FTF) versus ACASI modalities for improving honest responses, independent data from VOICE indicate that none of the behavioral assessments in the trial had any accuracy in estimating product use [8, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…Equally challenging is the consistent over-reporting of product use, which gives false impressions during trial implementation, and limits researchers’ ability to estimate efficacy in intent-to-treat and subset analyses. Growing evidence of a stark discrepancy between self-reported accounts of product use, and biologic or pharmacokinetic evidence of drug present in plasma [2, 6–8], demands that clinical trialists critically examine the reasons research participants are compelled to over-report and misrepresent their actual product use [9]. Put more simply, why do participants misreport adherence?…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two behavioral adherence measures, audio computer‐assisted self‐interviewing (ACASI) and clinic product counts (CPC), were found to be less than 50% accurate at predicting nonadherence in the VOICE trial . This poor predictive ability warrants consideration of objective measures for adherence monitoring in prevention studies.…”
Section: Adherence Measuresmentioning
confidence: 99%
“…Measuring adherence to PrEP regimens has relied primarily on participant self-report that can be unreliable (e.g., overreporting, recall issues, social desirability) or blood ARV concentrations that may not provide accurate measures of cumulative drug exposure over extended periods of use [2]. HIV PrEP interventions currently in development include multipurpose vaginal rings containing ARVs to prevent sexual transmission of HIV in addition to hormonal contraceptives to prevent pregnancy [3].…”
Section: Introductionmentioning
confidence: 99%
“…HIV PrEP interventions currently in development include multipurpose vaginal rings containing ARVs to prevent sexual transmission of HIV in addition to hormonal contraceptives to prevent pregnancy [3]. New analytical approaches to assess adherence to multipurpose vaginal rings are needed to better evaluate the safety and efficacy of these new intervention strategies [2,4,5]. Residual levels of the ARV dapivirine in used vaginal rings have recently been used to inform measures of adherence and efficacy for vaginal rings in clinical trials for HIV prevention [5,6].…”
Section: Introductionmentioning
confidence: 99%